Protection of MP3 music files using digital rights management and symmetric ciphering - Serrão, C.; Serra, A.; Dias, M.; Delgado, J. (2006 Second International Conference on Automated Production of Cross Media Content for Multi-Channel Distribution (AXMEDIS'06), 2006)
This paper presents part the work conducted on the 1ST FP6 MediaNet Integrated Project to implement a Media Center solution integrated in a home netwok environment. This Media Center solution - which was called MediaBox $allowed the user to access from his/her home to DRM-protected music from online digital music stores. The paper describes the specific work that was conducted in the protection of the MP3 music files and on the specific mechanisms of the DRM platform. These DRM mechanisms allow both the protection of the music file as well as the conditional music rendering at the end-user side, on a client-side platform - the MediaBox